Psychological Mindedness, Personality and Creative Cognition. Issue 1 (2nd January 2018) - LeBoutillier, Nicholas; Barry, Richard
Abstract : Research into psychological mindedness (PM) has focuses on its beneficial role in improving physical and mental well-being. The aim of this study was to investigate the role of two PM measures and personality in predicting creative cognition performance. Following the completion of a battery of questionnaires, 176 participants from the general population (age ranged from 16 to 68 years old) completed 3 creative cognition tasks. Hierarchical multiple regression analyses revealed independent effects for both the PM interest and insight variables in performance on 2 of the 3 creative cognition measures. Critically, these showed that the PM variables positively predicted performance on both the Creative Visualization Task and the Remote Associates Test. Conversely, the association between performance on the Alternate Uses Task and the PM variables was explained by the openness to new experience variable. These findings are discussed in the context of the inclusion of further mediating variables that may explain the causal relationship between PM and creative cognition.